Online Capacitance Monitoring for DC/DC Boost Converters Based on Low-Sampling-Rate Approach - Zhao, Zhaoyang; Davari, Pooya; Wang, Yaoqiang; Blaabjerg, Frede (IEEE journal of emerging and selected topics in power electronics, 2022)
Aluminum electrolytic capacitor (Al-Cap) is widely used in dc/dc converters to suppress voltage ripple and store energy to stabilize the output voltage. However, Al-Cap is one of the most vulnerable parts in power electronic converters, and its capacitance ( C ) is an important parameter for indicating the health status. For the purposes of condition monitoring (CM), small-signal voltage and current ripples are usually used to estimate the capacitance of Al-Caps. Unfortunately, the ripples of dc/dc converters have the features of small amplitude and high frequency, which increases the complexity for data acquisition and processing. Moreover, the amplitude of ripple changes as the operation condition of converters changes (e.g., the load changes), and it will increase the complexity of sampling circuits. Considering this issue, this article proposes a transient charging profile-based capacitance estimation scheme for dc/dc boost converters, which aims to reduce the sampling frequency. Taking a 24-48-V boost converter as a case study, simulation and experimental results demonstrate the feasibility of the proposed scheme for converters with different operating conditions and circuit parameters, and the estimation error is less than 3%.